PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHRAE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 016 SEKELADI - Mariyani Mariyani; Munjiatun Munjiatun; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research was aimed to increase students achievement of social lesson in III grade year of 2014/2015. The subject of this research in students III grade of state SDN 016 Sekeladi which is total of 20 students, consisted of 8 girls and 10 boys. This was a classroom research which has two cycles which was conducted on March 16th to April 09th 2015. The data shown that either learning process or students achievement increased. This was found from students and teachers scores in learning process increased. First cycle at the first meeting teacher’s activity was 66,67%categorized as good and increased 5,55% at the second meeting as 72,22% categorized as good. Meanwhile at the second cycle at the first meeting the percentage of teacher’s activity increased as 83,33% categorized as very good and in the second meeting it increased as 8,34% so the percentage became 91,67% categorized as very good. While students activities in learning process also increased. At the first cycle in the first meeting, the percentage of students activities was 61,11% categorized as good and the second meeting it increased as 5,56% so became 66,67% categorized as good. At the second cycle in the first meeting it increased to 80,56% categorized as very good. At the second meeting the percentage of students’ activities increased as 8,33% became 88,89% categorized as very good. However, students’ achievement also increased. The basic score of daily examination as 13,2% which 11 students passed and 13 students failed. The ending of daily examination was 61,11% and the average 71,67 on the passing grade. The second daily examination also increased from basic score of as13,2% which 15 students passed and 3 students failed. The ending of second daily examination was 83,33% and the average was 81,11. Based on the explanation above it can be concluded that the implementation cooperative learning by think pair share (TPS) to increase students achievement in social lesson of students III grade of State SDN 016 Sekeladi.Key Words : Cooperative Learning Think Pair Share (TPS) Thype, Social Lesson Learning Outcomes